Sex without consent: rape and sexual coercion in America - Smith, Merril D. (New York University Press, 2001)
"None of the women were abused" : indigenous contexts for the treatment of women captives in the Northeast / Alice Nash -- "Playing the rogue" : rape and issues of consent in seventeenth-century Massachusetts / Else L. Hambleton -- Sexual consent and sexual coercion in seventeenth-century Virginia / Terri L. Snyder -- Coerced sex and gendered violence in New Netherland / James Homer Williams -- Rape, law, courts, and custom in Pennsylvania, 1682--1800 000 / Jack Marietta and G.S. Rowe -- "The law should be her protector" : the criminal prosecution of rape in Upper Canada, 1791--1850 / Patrick J. Connor -- "I was very much wounded" : rape law, children, and the Antebellum South / Diane Miller Sommerville -- "A most detestable crime" : character, consent, and corroboration in Vermont's rape law, 1850--1920 / Hal Goldman -- "In the marriage bed woman's sex has been enslaved and abused" : defining and exposing marital rape in late-nineteenth-century America / Jesse F. Battan -- Race, honor, citizenship : the Massie rape/murder case / Bonni Cermak -- "Another negro-did-it crime" : black-on-white rape and protest in Virginia, 1945--1960 / Lisa Lindquist Dorr -- Sexual coercion and limited choices : their link to teen pregnancy and welfare / Robert Cherry -- Rape on campus : numbers tell less than half the story / Julie Campbell-Ruggaard and Jami Van Ryswyk